Italy : Financial System Stability Assessment, including reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Payment Systems, Insurance, Securities Regulation, Securities Settlement and Payment Systems, Monetary and Financial Policy Transparency, and Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses key findings of the Financial System Stability Assessment for Italy. The assessment reveals that Italy's financial system is sound, and no major vulnerabilities that could cause systemic risks are identified. The deep restructuring of the banking sector in the 1990s has helped improve the efficiency and competition of the Italian banking industry. Most standard performance indicators are now broadly in line with those of other large European countries. Competition in the Italian banking sector has not yet been fully reflected in the pricing and quality of core services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet